PENGARUH UKURAN PARTIKEL BUBUK DAN KONSENTRASI PELARUT ASETON TERHADAP KARAKTERISTIK EKSTRAK WARNA Sargassum polycystum - Noviantari, Ni Putu; Suhendra, Lutfi; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 3 (2017): September, 2017)
Sargassum polycystum is one type of brown seaweed from Indonesia that has potential as natural dye. The aims of this study were to determine the effect of particle size of powder and concentration of acetone solvent on characteristics color extract from Sargassum polycystum and to determine the best particle size of powder and concentration of acetone solvent to produce Sargassum polycystum color extract. The experiment in this study used Randomized Block Design (RBD) with two factors. The first factor is particle size of powder consisting of three levels: <40, 40, and 60 mesh. The second factor is the concentration of acetone solvent consisting of 4 levels:  65, 75, 85, and 95%. The results showed that the particle size of powder and concentration of acetone solvent affected significantly (P<0.01) on rendement, total carotenoid, total phenolic, brightness level (L*), redness level (a*) and yellowishness (b*). Interaction of both treatments affected significantly (P<0.01) on total carotenoid, total phenolic, redness level (a*) and yellowishness (b*), significant on rendemen (P<0.05), and did not effected (P>0.05) on brightness level (L*). The best treatment that produced color extract of Sargassum polycystum was obtained on particle size of powder from 60 mesh and concentration 95% of acetone solvent, which can produce 1.41% of rendement, 0.19% of total carotenoid, 16.02 mg GAE/ 100g of total phenolic, with brightness level (L*) 4.41, redness level (a*) -2.73 and yellowishness (b*) 38.66. Keywords : concentration of acetone solvent, the particle size of powder, Sargassum polycystum